Interfaith Marriage According To Customary Law In Kepau Baru Village, Tebing Tinggi Sub-District, Meranti Islands Regency - Safri, Agusti; Dasrol, Dasrol; Darnia, Meriza Elpha (Jurnal Ilmiah Wahana Pendidikan, 2026)
In general, interfaith marriages have the potential to cause legal problems, both for the married couple and for third parties, including the inheritance rights of children born from interfaith marriages. As a village with the largest number of religious adherents in Tebing Tinggi Timur Sub-district, Kepau Baru Village is also a village that is very thick with its customary law, of course in terms of marriages of different religions it cannot be avoided so that the role of the local customary leader and customary rules is needed. Therefore, the purpose of this research is first, to find out the provisions of interfaith marriages according to the Customary Law of Kepau Baru Village. Secondly, to find out the consequences of interfaith marriage according to the Customary Law of Kepau Baru Village. The type of research used in this research is sociological. The approach used by researchers is the type of sociological research. The location of the research conducted by the author is in Kepau Baru Village, East Tebing Tinggi District, Meranti Islands Regency. The population and samples in this study were the tribal chief/datuk and the perpetrators of interfaith marriages. This research uses data in the form of primary data and secondary data and data collection techniques are carried out by interview. The results of this research have two main points that can be concluded. First, the customary provisions in Kepau Baru Village for interfaith marriages must go through several stages, namely choosing one of the religions to be embraced, having been approved by both parents and the customary leader. Interfaith marriage in Kepau Baru Village requires a long process. Nevertheless, in this case, interfaith marriage according to Kepau Baru's custom is contrary to freedom of religion. Secondly, there are no major consequences of interfaith marriages in Kepau Baru Village, either in marriage registration or population data. If there are household problems in Kepau Baru Village, they are resolved by going to the customary leader for advice.